Abscess of the spleen in typhoid fever: clinical and morphological interpretation of the complication - A. N. Kovalenko; V. V. Kolkutin; A. V. Kovalev; V. A. Zinserling; A. A. Murachev (Журнал инфектологии)
Abscess of the spleen refers to an unusual complication of typhoid fever. Clinical and pathomorphological observation of cases of this complication are few and mainly relate to the regions with the epidemic spread of typhoid fever. Up to the present time there is no single point of view on the pathogenesis of this condition. Experience in diagnosis and treatment of such complication in young man is presented in this article. The diagnostic algorithm included the use of ultrasound diagnostics, computerized tomography and magnetic resonance imaging. Clinical and morphological interpretation of this complication, considered it as a rupture of a cavity in the spleen, was performed on the basis of the detailed histological examination. The cause of the complication was a congenital dysplastic abnormality – angioma of the spleen.